Happiness education and the Free Year Program in South Korea. Issue 2 (3rd April 2021) - Kim, Sung won; Kim, Lois Y.
ABSTRACT: Despite the widespread education reform discourses attempting to alleviate high-stakes examination pressure and narrowly test-driven education systems in East Asia, none have been as systematic and drastic as the Free Year Program (FYP) recently implemented in South Korea. The FYP provides middle school students with a year-long reprieve from examinations during which they can pursue other activities outside of the rigid test-oriented curriculum, exploring their career paths, free from the pressures of taking the midterm and final exams. In this article, we explore the contradictions raised by the discourse promoting the FYP within the broader national 'Happiness Education' framework. The FYP frequently references foreign cases, and articulates a national imaginary caught in between multiple competing agendas: the cultivation of a modern neoliberal subject in pursuit of their own happiness versus a collective nationalistic agenda in pursuit of global competitiveness, and multiple competing Western-inspired and domestic education discourses.